Adaptation of buildings to climate change: an overview - Saifudeen, Aysha; Mani, Monto (Frontiers in Built Environment, 2024)
Buildings worldwide have evolved based on local resources and skills, evolving form and orientation to ensure a productive and comfortable indoor environment. Traditional habitations rely on passive climate-responsive mechanisms and physiological resilience. At the same time, contemporary buildings rely increasingly on active mechanisms for fine-tuned convenience and comfort. Those buildings are becoming less habitable due to climate change. This paper presents an overview of research into climate-responsive building adaptation, identifying various factors determining a building’s ability to regulate external climatic conditions in providing a habitable indoor environment. The review covers the ability of occupants to manage their thermal environment and adaptation mechanisms, including various adaptation strategies attributed to climate change. Besides a review of relevant research tools and methodologies, the paper also identifies future research challenges. Those challenges include but are not limited to evaluating climate classification provided by building standards given climate change, the need for region-specific climate-change vulnerability assessment of the built environment to develop specific adaptation strategies, a survey of vernacular structures to understand their inherent adaptation capacities, developing a framework to study building adaptation, etc. Thus, this review opens the possibility of further research in building adaptation.